Clinical Characteristics and Risk Factors Analysis of COVID-19 Infections- A Single Center Observational Study - Bhuiyan, Mohammad Abdul Quddus; Alam, Md Zukfikkar; Nabi, Md Nurun; Munir, Umar Rashed (Journal of Armed Forces Medical College, Bangladesh, 2023)
Introduction: COVID-19 emerged as a major public health outbreak in late 2019. Bangladesh reported its first case on 8th March 2020 and at Sylhet Div area, first case detected in April 2020, authority adopted a policy of extensive contact tracing, quarantine and initially hospitalizing of all cases. Clinical characteristics of COVID-19 cases have been described as per national and WHO guideline. Objectives: To analyze clinical characteristics and the risk factors of COVID-19 infection. Methods: Clinical records of all COVID-19 confirmed cases aged ≥12 years admitted to COVID Unit or treated at home isolation with complete outcomes at Sylhet area were included in the study. Duration of this study was 1st April to 27th December 2020. Epidemiological history, comorbidities, clinical features, investigations, management and complications of all cases were recorded in preform data sheet and analyzed. Variables were compared between mild and severe diseases. Results: The sample comprised of 515 cases (mean age 30.98 years, male 81.55%). Majority were mild (92%) and 6.4% required intensive care, with 85% admitted within the first five days. Older age (≥51 years), underlying comorbidities, cough, breathlessness, reduced oxygen saturation and abnormal chest radiographs on admission were significant determinants for severity. The case fatality rate was 0.77% and the four commonest complications were ARDS (4.40%). liver injuries (4.07%), bacteraemia (2.33%) and kidney injuries (1.16%). Conclusion: Lower case fatality rate was possibly contributed by young cases with mild diseases and early hospitalization. Abnormal chest radiographic, elderly and other comrbidities require frequent measurement of oxygen saturation with pulse oximetry and close monitoring within the first few days to detect early deterioration and to take appropriate measures. Ivermectin seems to be effective in the treatment of Covid-19 infection but need further large multi-center case control study. JAFMC Bangladesh. Vol 18, No 2 (December) 2022: 19-23